PENERAPAN PRINSIP-PRINSIP GOOD GOVERNANCE TERHADAP PELAYANAN PUBLIK DI DESA BANUA KECAMATAN BUNGIN KEBUPATEN ENREKANG - Rosnani; Tajuddin, Sapri; Hardianti (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
The aim of the research is to determine the application of good governance principles to public services in Banua village, Bungin sub-district, Enrekang district, to determine supporting and inhibiting factors in the application of good governance principles to public services in Banua village, Bungin sub-district, Enrekang district. The population of this study was 194 heads of families in Banua village. The sample in this research was 66 heads of families, taken based on non-probability sampling techniques. The type of this research is quantitative descriptive. Data collection techniques used were observation, interviews, literature study and questionnaires. The data analysis technique used is validity, reliability and simple linear regression using the help of the IBM SPSS Statistics 21.0 application. The research results show that the implementation of Good Governance principles in Banua village is in the